Praxisorientierte, rationale Anämieabklärung: CME : zertifizierte Fortbildung - Metzgeroth, Georgia; Hastka, Jan (Die Innere Medizin, 2025)
Anemia is frequently diagnosed in the daily clinical routine and is an indicator of a more or less severe underlying disorder. An understanding of the diverse and complex etiology is crucial for a practice-oriented diagnostic approach. In principle, there are many differential diagnoses. The diagnosis is further complicated by the fact that anemia is often multifactorial, especially in old age. A rational clarification of anemia takes epidemiological data and the individual medical history into account. Classification according to erythrocyte indices plays a central role. The most important cause of hypochromic microcytic anemia is iron deficiency, with thalassemia and anemia of chronic disorders (ACD) as differential diagnoses. Hyperchromic macrocytic anemia is mainly caused by disturbances of vitamin B12 and folic acid metabolism or the DNA synthesis. The group of normochromic normocytic anemias includes most of the subtypes of anemia. In unclear cases, a referral to a hematologist for clarification is recommended.